Effect of Age on Employees’ Loyalty: a Study Among the Executives’ of a Large Scale Public Sector Manufacturing Industry Across India - ., Geevarghese; J.T Nirmalraj, R; Seeram, Hemalatha; Veena, S; James, Beena (International Journal of Engineering and Technology, 2018)
The nature of human resources and their willingness to contribute have an impact on the existence and growth of the organization. Employee loyalty may be defined as employees being committed to the success and growth of the organization and believing that working for this organization is their obligation and best option available to them. The growth and success of organizations in the present scenario, largely depends upon the commitment and loyalty of its workforce. As employees work for the organizations for certain period of time, they develop affinity and emotional attachment to the organization. As they grow older their maturity level will increase and stop job hopping. Further, as the age of the employee increases, they will try to settle down in one place and the probability of their intention to stay with the organization also will increase which in turn will influence their loyalty to the organization.Â Therefore, age of an employee is generally considered as a factor influencing loyalty to the organization.The purpose of this paper is to investigate the effect of age of employee on employeesâ€™ loyalty in a Bangalore based large scale public sector undertaking. 200 middle level executives who have completed minimum of one year service were surveyed and random sampling technique was adopted. Survey was conducted with a standardized, valid and reliable instrument measuring loyalty. The detailed findings and implications are discussed in the full paper.Â Â